Implementasi Augmented Reality Berbasis Google Lens sebagai Media Pembelajaran Perancangan Desain Interior 3D Modern - Annisa, Putri; Riadi, Rizka Salsabila (Journal Global Technology Computer, 2025)
Learning modern interior design, as an effort to develop students' creativity, requires innovation in the interaction media between students and learning materials. Currently, the use of Augmented Reality (AR) in design education is becoming increasingly relevant and gaining attention as an interactive learning medium. However, several challenges remain, including hardware limitations, a lack of realistic visualization, and the need for a more immersive learning experience. The proposed solution is the utilization of Google Lens as an AR-based platform to access 3D interior design models directly via mobile devices. This approach employs a simple marker-based tracking method, where visual markers or specific objects trigger the visualization of 3D in the real environment. Students can point their smartphone cameras at the marker to access the designs, interact with spatial elements, and better understand the structural and aesthetic concepts of interior spaces. This creates a more immersive, creative, and dynamic learning experience. The results of this study show that the implementation of Google Lens-based AR enhances students' spatial understanding, learning motivation, and engagement in the interior design process. Moreover, it provides an accessible and effective learning tool, opening new opportunities for the development of immersive technology-based learning methods.